Measure and analyze the cost of total quality in the General Company for Electrical Industries - ali qasim hassan (Iraqi Journal for Administrative Sciences, 2024)
Is the cost of total quality is an important part of the total cost final product and the importance of not less than the importance of costs of industrial, marketing and management of the final product as most industrial companies to ascertains its goals once the production only, but by offering a product with high quality and cost of suitable, so have dealt with this research subject of measurement and analysis total cost of total quality has been selected the General Company for electrical Industries sample to search. as the main objective of the research is the measurement and analysis of the total cost overall quality of the company sample by drawing on the subcategory of these costs and reliance on one of the indicators used to measure the cost overall quality and to achieve the goal of the research adopted a research hypothesis basic to the effect that measure and analyze the total cost of total quality lead to the provision of accounting information and analytical minutes help the company sample to control cost and quality of their products and help them to provide high quality products meet the wishes of customers and achieve maximum sales and profits are possible. I have concluded this research a set of conclusions and recommendations that can contribute to the upgrading of the quality of the company's products and the cost of the research sample and help them to excel and achieve their goals as required and correct.